A taste for the wild - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Why should so much attention be given to beef and chicken when many wild animals could be used to provide more flavoufful protein at a lower cost ? According to recent research, game ranching and the raising of small, wild animals that are both...